Catalytic activation of peroxymonosulfate with manganese cobaltite nanoparticles for the degradation of organic dyes. Issue 7 (22nd January 2020) - Dung, Nguyen Trung; Thu, Tran Viet; Van Nguyen, To; Thuy, Bui Minh; Hatsukano, Masahito; Higashimine, Koichi; Maenosono, Shinya; Zhong, Ziyi
Abstract : Catalytic degradation of organic dyes via manganese cobaltite nanoparticles-activated peroxymonosulfate. Abstract : In this work, we report the facile hydrothermal synthesis of manganese cobaltite nanoparticles (MnCo2 O4.5 NPs) which can efficiently activate peroxymonosulfate (PMS) for the generation of sulfate free radicals (SO4 ˙ − ) and degradation of organic dyes. The synthesized MnCo2 O4.5 NPs have a polyhedral morphology with cubic spinel structure, homogeneously distributed Mn, Co, and O elements, and an average size less than 50 nm. As demonstrated, MnCo2 O4.5 NPs showed the highest catalytic activity among all tested catalysts (MnO2, CoO) and outperformed other spinel-based catalysts for Methylene Blue (MB) degradation. The MB degradation efficiency reached 100% after 25 min of reaction under initial conditions of 500 mg L −1 Oxone, 20 mg L −1 MnCo2 O4.5, 20 mg L −1 MB, unadjusted pH, and T = 25 °C. MnCo2 O4.5 NPs showed a great catalytic activity in a wide pH range (3.5–11), catalyst dose (10–60 mg L −1 ), Oxone concentration (300–1500 mg L −1 ), MB concentration (5–40 mg L −1 ), and temperature (25–55 °C). HCO3 −, CO3 2− and particularly Cl − coexisting anions were found to inhibit the catalytic activity of MnCo2 O4.5 NPs. Radical quenching experiments revealed that sulfate radicals are primarily responsible for MB degradation. A reaction sequence for the catalytic activation of PMS was proposed. The as-prepared MnCo2 O4.5 NPs could be reused for at least three consecutive cycles with small deterioration in their performance due to low metal leaching. This study suggests a facile route for synthesizing MnCo2 O4.5 NPs with high catalytic activity for PMS activation and efficient degradation of organic dyes.